Reductive leaching of low-grade manganese ores from Way Kanan using corncob as reductant - Putri, Yolanda Dwika; Lesmana, Donny; Ginting, Simparmin Br; Sujoto, Vincent Sutresno Hadi (Jurnal Rekayasa Proses, 2023)
The processing of mining products in indonesia has not been utilized optimally. One of them is manganese ore. Way kanan is one of indonesia's potential manganese ore sites. The manganese leaching study used a -200 mesh way kanan manganese ore that was reacted with sulfuric acid at concentrations of 0.1 M, 0.5 M, and 1 M, as well as corncob as a reductant. To separate the dissolved iron in the leaching process, the manganese sulfate solution was purified with sodium hydroxide and then filtered to have a manganese sulfate solution free of iron. Manganese was precipitated using oxalic acid. The manganese oxalate precipitation was calcined at a temperature of 350 °c for two hours. The best manganese extraction obtained at 92.3% was at a sulfuric acid concentration of 1 M, a temperature of 80 °c, and a solution volume of 400 ml. Calcination of manganese oxalate converted the material into hausmannite (Mn3O4).